Strip-loaded nanophotonic interfaces for resonant coupling and single-photon routing - Snow, Katharine; Moradiani, Fatemeh; Siampour, Hamidreza (Frontiers in Physics, 2024)
We report on the design and simulation of strip-loaded nanophotonic interfaces aimed at improving resonant coupling and photon routing efficiency. In our design, the guided mode is confined within a plane by a high-index thin film and is loosely confined laterally by a lower index strip. Using a hydrogen silsesquioxane (HSQ) strip, titanium dioxide core, and silicon dioxide substrate, we optimise the waveguide dimensions for maximum lateral confinement of light. Specifically, we propose a polymerbased Bragg grating cavity and ring resonator that achieve near-optimal mode volumes and high Q-factors. These may be further developed to achieve the even higher Q-factors demanded by quantum technologies. Our calculations suggest that a quantum dot embedded in a cavity with a mode volume of 𝑉 𝑒𝑓𝑓 ~7.0(𝜆/𝑛) 3 and a Q-factor of 7000 can produce photons with 97% indistinguishability at 4K. Additionally, we investigate directional couplers for efficient photon routing, comparing photonic and plasmonic material structures. While pure photonic structures demonstrate lower loss and improved quality factors, they face practical limitations in terms of bending radius. Conversely, plasmonic structures offer shorter bending radii but higher propagation losses. This research lays the groundwork for future nanophotonic designs, aiming to enhance photon generation and routing capabilities for quantum optical applications.